Effect of Effectiveness of Accounting Information System on Individual Performance with Personal Technique Capability as Moderate - Gunawan, I Made Putra Adi; Tenaya, Agus Indra (E-Jurnal Akuntansi, 2017)
Accounting Information System is a system designed with the aim to assist data processing and information in the field of economic or corporate finance. This is because the company desperately needs information to be able to take a decision, so there needs to be a system that can provide the necessary information accurately, relevant and timely. In addition to the availability of a good system, system users are also required to have adequate capabilities, so as to utilize the system to its full potential. Therefore, this study aims to examine the effect of effectiveness of accounting information systems on individual performance and to determine the ability of personal techniques in moderating the influence of effectiveness of accounting information systems on the individual performance of Lembaga Perkreditan Desa in Denpasar. The study was conducted on 35 LPD in Denpasar, with a population of 420  employees. Sample selection method using purposive sampling method is the determination of based on the suitability of certain characteristics so that the sample obtained as many as 105 respondents. Data collection method used is questionnaire method, then data analysis technique used is moderating regression analysis (MRA) technique. Based on the results concluded that the effectiveness of accounting information system has a positive effect on individual performance and the ability of personal technique on accounting information system able to moderate influence effectiveness of accounting information system to individual performance at Lembaga Perkreditan Desa in Denpasar. Keywords : Personal technical ability, effectiveness of accounting information system,  individual performance